Mudanças na diversidade de macroinvertebrados associadas com uma piscina em um riacho de primeira ordem no nordeste do Pará - LIMA, Jeovana Oliveira (2022)
The Amazon region is known for its great diversity of fauna and flora, and the interaction between forests, rivers, and streams that creates a rich ecosystem. First order streams, due to their smaller width, are usually covered by a riparian forest. This causes a large influx of leaves, branches, and fruits that end up acumulating on the bottom of these streams and forming a wide range of food sources and microhabitats; the latter serve as a refuge for various aquatic organisms. Macroinvertebrates are organisms that, for at least part of their lives, live associated with benthic habitats. Their mode of life, feeding, interaction with the water and substrates, and their ecological role make them excellent and cost-effective models for study especially in rapid environmental assessment and biomonitoring. The presence, absence, or a certain level of abundance of a macrobenthic taxon can help categorize aquatic environments. Work with functional feeding groups (FFG) of macroinvertebrates is aimed at environmental assessment, and its methodology is based on the feeding behavior of these organisms. In northern Brazil, it is very common to use rivers and streams for leisure. The popular bathing resorts receive bathers frequently, and because they are so popular, some small creeks have their structure modified. The most common is to transform a stretch of stream into a swimming pool, which clearly affects stream hydrodynamics. The objective of this work is to investigate whether the pool is affecting the taxonomic and functional diversity of aquatic macroinvertebrates. Samples were collected upstream (above) and downstream (below) of the pool. Two sediment samples were collected, one for sorting and identification of individuals, and one for grain size. All organic matter present in the screening replicate was separated and weighed for analysis. Macroinvertebrates were sorted, identified to family, allocated to functional group, and counted in the laboratory. Water, sediment, and macroinvertebrate data analyses were performed with GNU R version 4.2.1 (R Core Team, 2022). The two areas, Upstream and Downstream of the pool were shown to be different in terms of the fauna, and the highest richness and abundance values were associated with environmental variables such as oxidation-reduction potential, gravel, coarse sand or fine sand and total organic matter. The results with GFA were similar to the taxonomic groups. Therefore, our work proved to be efficient in evaluating this stretch of the creek regarding the changes in the composition of the benthic macrofauna in relation to the pool.